Ultrablack color in velvet ant cuticle - Vinicius Marques Lopez; Wencke Krings; Juliana Reis Machado; Stanislav Gorb; Rhainer Guillermo-Ferreira (Beilstein Journal of Nanotechnology)
We studied the ultrastructure of the ultrablack cuticle in Traumatomutilla bifurca, an enigmatic and visually striking species of velvet ants (Hymenoptera, Mutillidae). Using a combination of scanning electron microscopy (SEM), transmission electron microscopy (TEM), confocal laser scanning microscopy (CLSM), and optical spectroscopy, we conducted a comprehensive analysis of the cuticle to elucidate its unique optical properties. SEM imaging provided a detailed surface morphology, while TEM provided insights into the internal structure. CLSM showed that the cuticle exhibits no autofluorescence. Our findings reveal a highly specialized cuticle, characterized by microstructures that effectively minimize reflectance and enhance light absorption. Optical spectrometry confirmed the ultrablack nature of the cuticle, with the measured reflectance approaching minimal levels across a broad spectrum of wavelengths. Therefore, our study contributes to a deeper understanding of ultrablack biological materials and their potential applications in biomimetics.